2015
DOI: 10.1002/zaac.201500532
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectroscopic Investigation of FeII and FeIII 3,4,5‐Trihydroxybenzoates (Gallates) – Proposed Model Compounds for Iron‐Gall Inks

Abstract: Abstract. Iron gallates with iron in the oxidation states Fe 2+ and Fe 3+were prepared and studied by Mössbauer spectroscopy, X-ray diffraction, and IR spectroscopy. Fe III 3,4,5-trihydroxybenzoate (gallate) Fe(C 7 O 5 H 4 )·2H 2 O, whose structure was first determined by Wunderlich, was obtained by the reaction of gallic acid and metallic iron or by oxidation of the Fe II gallate, which was obtained by the reaction of ferrous sulfate with 3,4,5-trihydroxybezoic acid (gallic acid) under anoxic conditions. Tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…In agreement with Lerf and Wagner [14,15], the data gathered show that the main chromophore in the iron-gall inks we reproduced is not based on a carboxylate-iron binding, as suggested in previous literature, including the recent work by Ponce et al [6,11,12]. As an alternative to iron-carboxylate binding, colour may be developed through the catechol ring, with 2 OH or galloyl with 3 OH groups providing binding sites for metal ions to chelate, as has already been proposed in different scientific areas of research [38; also see 4,7,8,13].…”
Section: Microftir Spectroscopysupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with Lerf and Wagner [14,15], the data gathered show that the main chromophore in the iron-gall inks we reproduced is not based on a carboxylate-iron binding, as suggested in previous literature, including the recent work by Ponce et al [6,11,12]. As an alternative to iron-carboxylate binding, colour may be developed through the catechol ring, with 2 OH or galloyl with 3 OH groups providing binding sites for metal ions to chelate, as has already been proposed in different scientific areas of research [38; also see 4,7,8,13].…”
Section: Microftir Spectroscopysupporting
confidence: 89%
“…From polyphenol research, it has been shown that "tannins" are found in galls largely as polygalloyl esters of glucose depicted in Fig. 2 [10], however the models used by the scientific community to describe the iron complexes assume that gallic or tannic acids are available in the gall extracts to bind iron [6,[11][12][13][14][15] (Fig. 2 and Additional file 1: Fig.…”
Section: Polyphenol Metal Ion Complex: the Ligandsmentioning
confidence: 99%
“…Whereas the structure and magnetic properties of these transition metal based solids were thoroughly studied, 23,27 no information about their adsorptive properties was available. Nitrogen sorption experiments carried out at 77 K on the Mg derivative indicated that this solid is microporous, although the small size of the pores and their high polarity, associated with the presence of remaining acidic protons on the ligand, accounted for strong diffusion kinetics limitation at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the state of the iron even on freshly written manuscripts is mainly the result of the reaction of the cellulose of the paper and the unreacted iron sulfate of the ink. The concentration of complexes of iron with phenolic ligands is, at least in most cases, too low to be seen in the Mössbauer spectra [40]. In the course of time, and depending on the conditions of storage, iron oxalate or iron oxy-hydroxides may form from the iron compounds formed initially with the cellulose of the paper.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that polyphenol complexes of the inks decompose to Fe(II)-oxalate with iron from the iron sulfate. For example, a ferrous component found as a byproduct in the synthesis Fe(III)-gallate(2) from ferrous sulfate and gallic acid at about 100 °C [40] is clearly ferrous oxalate. The exact conditions under which ferrous oxalate forms in old documents still need clarification, but prolonged storage in a warm and moist environment may be favorable for its formation.…”
Section: Papers With Applied Inkmentioning
confidence: 99%